The Role of Kharkiv State Academy of Culture in Training Foreign Specialists in Library Science - Al-Qsous, Inaya (ХДАК, 2025)
My name is Inaya, and I am from the Hashemite Kingdom of Jordan. I completed my school education in Jordan, in the city of Karak, in the south of the country. At that time, it was difficult for me to enroll in university studies in Jordan because of financial circumstances. Fortunately, I got an opportunity to become a student of the Institute of Culture in the city of Kharkiv, where I studied for five years at the Faculty of Library Science, and graduated with a specialization in Library Management.
Keywords: бібліотечно-інформаційна освіта; Харківська державна академія культури; Kharkiv State Academy of Culture